In the quiet, noisy woods - Rosen, Michael J., 1954-; Won, Annie (New York : Doubleday, 2019)
A forest's quiet chorus of chirps, clicks, and chits change to loud scree-scree-screeches and other noises as two rambunctious wolf pups, separated from their pack, scamper and chase.
Keywords: Animal sounds -- Fiction; Forest animals -- Fiction; Forests and forestry -- Fiction; Wolves -- Fiction; Animals -- Infancy -- Fiction